Convergence of output and wages in Europe - Jordán, Lukáš; Potužák, Pavel; Špecián, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
The diploma thesis aims to analyse the convergence within Europe. The analysis of convergence is done in the sense of β and σ as well, not only for real output per capita but also for wages. The neoclassical model of growth (the RCK model) predicts the unconditional convergence of -0.020 and -0.068 for α amounts to 0.70 and 0.35, respectively. Besides, it can be shown that the growth model implies σ-convergence. The graphical and empirical part verifies the presence of the convergence processes and also that the output is more converged than wages. The final speed equals to -0.017 and -0.040 for unconditional and conditional convergence, respectively. The speed of wage convergence is not precisely determined. The only finding of wages is that they converge faster than output. In addition, the σ-convergence is confirmed for both variables.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses